Discussion on Prevention Measures and Remedy Options in Evaluation of Flood Control - DONG Hui (Renmin Zhujiang)
With China's economic and social development and expanding urban infrastructure construction,there are more and more construction projects within the scope of river channel management.The project construction usually occupies the flood discharge section,produces backwater,changes the local flow regime,and destroys the embankment section,affecting the safety of flood discharge and embankments.At the same time,floods scour the river channel and endanger the safety of the project.The evaluation of flood control should be carried out,and prevention measures and remedy options should be implemented simultaneously with the construction projects to reduce the influence of river-related projects on the river channel and ensure the flood control safety of the projects.This paper analyzes the river-crossing project and estuary mouth in terms of river-related concern,the key points of technical review,and the influence mechanism.Combined with project examples,the paper summarizes the prevention measures and remedy options in various evaluations of flood control according to their characteristics,including the layout method,scope of implementation,and design principle.It can provide a reference for the similar evaluation of flood control.